PSD2 INFLUENCE ON DIGITAL BANKING TRANSFORMATION - BANKS’ PERSPECTIVE - Petrović, Marijana (Journal of process management and new technologies, 2020)
The European Union government has forced banks to open and make their customer information accessible with their permission, for other players in the financial market to use and take part of that business, in order to make the banking industry more innovative, stimulate new ideas in the payments market and better regulate existing legal frameworks for payment and banking services across the EU. This paper analyzes the impact that the revised PSD2 Directive has on the digital transformation of banking across the European Union.